Massive Survey on Bacterial–Bacteriophages Biodiversity and Quality of Natural Whey Starter Cultures in Trentingrana Cheese Production - Mancini, Andrea; Rodriguez, Maria Cid; Zago, Miriam; Cologna, Nicola; Goss, Andrea; Carafa, Ilaria; Tuohy, Kieran; Merz, Andrea; Franciosi, Elena (Frontiers in Microbiology, 2021)
This study focused on the microbial and bacteriophages identification and characterization in cheese-production facilities that use Natural Whey Starter (NWS) cultures for Trentingrana production. Bacterial and phage screening was carried out on cooked not acidified Whey (cNAW) and NWS samples isolated from six dairy factories, for three consecutive days in four different months. By means of a combined approach, using plate counts, bacterial isolation and meta-taxonomic analysis Lactobacillus helveticus was found occurring as the dominant species in NWS cultures, and Levilactobacillus brevis as co-dominant in the cheese-factories where the temperature of NWS production was mainly lower than 40°C suggesting that the variability in the parameters of the NWS culture preparation could differently modulate the bacterial species in NWS cultures. Using turbidity test approach on 303 bacterial isolates from the NWS cultures, 120 distinct phages were identified. L. helveticus phage contamination of NWS cultures was revealed in most of the analyzed samples but, despite the great recovery of bacteriophage contamination cases, the microbial quality of NWS cultures was high. Our results support the presence of natural bacteriophage resistance mechanisms in L. helveticus. The use of natural whey starter cultures probably creates an ideal environment for the proliferation of different L. helveticus strains balanced with their phages without a clear dominance. It is evident, from this study, that the presence of a high biodiversity of NWS bacterial strains is relevant to avoid phages dominance in NWS cultures and consequently to keep a good acidification ability.